Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper ;, 2005)
Reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations and proposes to extend the availability of the rights approach, which expires on August 31, 2005, by another year. The rights approach remains a potentially important element of the intensified collaborative approach for arrears clearance for the three members that remain eligible, Liberia, Somalia, and Sudan.